A brief intervention for drug use, sexual risk behaviours and violence prevention with vulnerable women in South Africa: a randomised trial of the Women's Health CoOp. Issue 5 (17th May 2013) - Wechsberg, Wendee M; Jewkes, Rachel; Novak, Scott P; Kline, Tracy; Myers, Bronwyn; Browne, Felicia A; Carney, Tara; Morgan Lopez, Antonio A; Parry, Charles
Abstract : Objective: To assess the impact of the Women's Health CoOp (WHC) on drug abstinence among vulnerable women having HIV counselling and testing (HCT). Design: Randomised trial conducted with multiple follow-ups. Setting: 15 communities in Cape Town, South Africa. Participants: 720 drug-using women aged 18–33, randomised to an intervention (360) or one of two control arms (181 and 179) with 91.9% retained at follow-up. Interventions: The WHC brief peer-facilitated intervention consisted of four modules (two sessions), 2 h addressing knowledge and skills to reduce drug use, sex risk and violence; and included role-playing and rehearsal, an equal attention nutrition intervention, and an HCT-only control. Primary outcome measures: Biologically confirmed drug abstinence measured at 12-month follow-up, sober at last sex act, condom use with main and casual sex partners, and intimate partner violence. Results: At the 12-month endpoint, 26.9% (n=83/309) of the women in the WHC arm were abstinent from drugs, compared with 16.9% (n=27/160) in the Nutrition arm and 20% (n=31/155) in the HCT-only control arm. In the random effects model, this translated to an effect size on the log odds scale with an OR of 1.54 (95% CI 1.07 to 2.22) comparing the WHC arm with the combined control arms. Other 12-month comparison measures between arms were non-significant for sex risk and victimisation outcomes. At 6-month follow-up, women in the WHC arm (65.9%, 197/299) were more likely to be sober at the last sex act (OR1.32 (95% CI 1.02 to 1.84)) than women in the Nutrition arm (54.3%, n=82/152). Conclusions: This is the first trial among drug-using women in South Africa showing that a brief intervention added to HCT results in greater abstinence from drug use at 12 months and a larger percentage of sexual activity not under the influence of substances. Trial registration number: NCT00729391 ClinicalTrials.gov